The Status of Industrial Relations as an Academic Discipline Within Canadian Universities - Boivin, Jean (Relations industrielles / Industrial Relations, 1992)
A survey on the status of industrial relations (IR) as an academic discipline in Canadian universities shows that even within business programs where serious efforts are made to adequately cover labor relations phenomena, there is an overwhelming exposure to human resource management (HRM) and organizational behavior (OB) activities and very little coverage of public labor policy. This is so because, from a business perspective, labor relations stands as a subfield of HRM. The fact that the employment relationship is just one of many foci for administrative science probably explains why business programs have a normative bias in favor of the efficiency principle. On the other hand, because the entire focus of IR is on the employment relationship, IR academic programs consider as equal values the equity needs of the employees and the efficiency needs of the organization. This ontological neutrality is what distinguishes the IR and administrative science disciplines.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Colleges & universities; Curricula; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Study & teaching; higher education